Protective effects of Descurainia sophia seeds extract and its fractions on pulmonary edema by untargeted urine and serum metabolomics strategy - Jinying Zhang; Ning Zhou; Ning Zhou; Yongxiang Wang; Tong Liu; Yumin Cao; Weisheng Feng; Weisheng Feng; Weisheng Feng; Xiaoke Zheng; Xiaoke Zheng; Xiaoke Zheng (Frontiers Media S.A., 2023)
Background:Descurainia sophia seeds (DS) is a herbal medicine in traditional Chinese medicine (TCM) for treating lung diseases. We aimed to evaluate the therapeutic effect of DS and five of its fractions upon pulmonary edema (PE) through metabolomics analysis (MA) of urine and serum samples of rats.Methods: A PE model was established by intrathoracic injection of carrageenan. Rats were pretreated with DS extract or its five fractions (polysaccharides (DS-Pol); oligosaccharides (DS-Oli); flavonoid glycosides (DS-FG); flavonoid aglycone (DS-FA); fat oil fraction (DS-FO)) for seven consecutive days. Forty-eight hours after carrageenan injection, lung tissues were subjected to histopathology. MA of urine and serum was done by ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry, respectively. Principal component analysis and orthogonal partial least squares-discriminant analysis were operated for the MA of rats and potential biomarkers related to treatment. Heatmaps and metabolic networks were constructed to explore how DS and its five fractions act against PE.Results: DS and its five fractions could all attenuate pathologic lung injury to different degrees, and DS-Oli, DS-FG, and DS-FO had a more potent effect compared with DS-Pol and DS-FA. DS-Oli, DS-FG, DS-FA, and DS-FO could regulate the metabolic profiles of PE rats, but DS-Pol was less potent. According to MA, the five fractions could improve PE to some degree due to their anti-inflammatory, immunoregulatory, and renoprotective activities by mediating the metabolism of taurine, tryptophan, and arachidonic acid. However, DS-Oli, DS-FG, and DS-FO had more important roles in edema-fluid reabsorption, and reduction of vascular leakage through regulating the metabolism of phenylalanine, sphingolipid and bile acid. Finally, heatmaps and hierarchical clustering analysis indicated DS-Oli, DS-FG, and DS-FO to be more efficacious than DS-Pol or DS-FA against PE. The five fractions of DS had a synergistic effect on PE from different aspects, thereby constituting the entire efficacy of DS. DS-Oli, DS-FG, or DS-FO could be used as an alternative to DS.Conclusion: MA combined with use of DS and its fractions provided novel insights into the mechanism of action of TCM.